Text-to-speech synthesis as an alternative communication means after total laryngectomy - Repova, Barbora; Zabrodsky, Michal; Plzak, Jan; Kalfert, David; Matousek, Jindrich; Betka, Jan (Biomedical papers, 2021)
Aims. Total laryngectomy still plays an essential part in the treatment of laryngeal cancer and loss of voice is the most feared consequence of the surgery. Commonly used rehabilitation methods include esophageal voice, electrolarynx, and implantation of voice prosthesis. In this paper we focus on a new perspective of vocal rehabilitation utilizing alternative and augmentative communication (AAC) methods. Methods and Patients. 61 consecutive patients treated by means of total laryngectomy with or w/o voice prosthesis implantation were included in the study. All were offered voice banking and personalized speech synthesis (PSS). They had to voluntarily express their willingness to participate and to prove the ability to use modern electronic communication devices. Results. Of 30 patients fulfilling the study criteria, only 18 completed voice recording sufficient for voice reconstruction and synthesis. Eventually, only 7 patients started to use this AAC technology during the early postoperative period. The frequency and total usage time of the device gradually decreased. Currently, only 6 patients are active users of the technology. Conclusion. The influence of communication with the surrounding world on the quality of life of patients after total laryngectomy is unquestionable. The possibility of using the spoken word with the patient's personalized voice is an indisputable advantage. Such a form of voice rehabilitation should be offered to all patients who are deemed eligible.
Keywords: voice rehabilitation; total laryngectomy; laryngeal cancer; voice banking; augmentative communication; quality of life